2019
DOI: 10.1152/ajpregu.00383.2018
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic activation of orexin/hypocretin neurons ameliorates aging-induced changes in behavior and energy expenditure

Abstract: Aging affects numerous physiological processes, as well as behavior. A large number of these processes are regulated, at least partially, by hypothalamic orexin neurons, and orexin tone may decrease with normal aging. In this study, we hypothesized that designer receptors exclusively activated by designer drugs (DREADD) stimulation of orexin neuronal activity will ameliorate the effect of aging on behavioral and metabolic alterations in young and middle-aged mice. DREADD targeting was achieved by stereotaxic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 92 publications
3
19
0
Order By: Relevance
“…The orexin system plays a major role in the regulation of physical activity (Zeitzer et al, 2004; Burgess, 2010). In our recent study (Stanojlovic et al, 2019), we observed that DREADD-induced activation of orexin neurons increased locomotion in both young, 5-month-old, and middle-aged, 12-month-old WT mice. In the current study, however, activation of orexin neurons did not have an effect on locomotion in A53T mice.…”
Section: Discussionmentioning
confidence: 76%
“…The orexin system plays a major role in the regulation of physical activity (Zeitzer et al, 2004; Burgess, 2010). In our recent study (Stanojlovic et al, 2019), we observed that DREADD-induced activation of orexin neurons increased locomotion in both young, 5-month-old, and middle-aged, 12-month-old WT mice. In the current study, however, activation of orexin neurons did not have an effect on locomotion in A53T mice.…”
Section: Discussionmentioning
confidence: 76%
“…For behavioral tests, 3 mg/kg of CNO in saline or saline was injected via a small gauge (32) syringe once 30 min prior to testing. For indirect calorimetry and SPA studies, animals were given CNO dissolved in drinking water (0.25 mg/mL) or drinking water [ 94 ]. This was necessary to leave unbroken the gas-exchange seal of the indirect calorimetry units.…”
Section: Methodsmentioning
confidence: 99%
“…Firoc mice were obtained by crossing Orexin‐Cre mice (a kind gift of T Sakurai, Tsukuba Univ, Japan) a mouse model extensively used, 29‐31 with IGF‐IR f/f mice (B6, 129 background; Jackson Labs; stock number: 012251; exon 3 floxed). Cre recombination of the floxed IGF‐IR results in deletion of exon 3, functional inactivation of the receptor 32 and substantial reduction of IGF‐IR expression 33 .…”
Section: Methodsmentioning
confidence: 99%